Review paperMedicinal plants used in treatment of inflammatory skin diseases - Dawid-Pać, Renata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Skin is an organ providing contact with the environment and protecting the human body from unfavourable external factors. Skin inflammation, reflected adversely in its functioning and appearance, also unfavourably affects the psyche, the condition of which is important during treatment of chronic skin diseases. The use of plants in treatment of inflammatory skin diseases results from their influence on different stages of inflammation. The paper presents results of the study regarding the anti-inflammatory activity of the plant raw material related to its influence on skin. The mechanism of action, therapeutic indications and side effects of medicinal plants used for treatment of inflammatory diseases of the skin are described.